Five new species of Ytu Reichardt (Coleoptera: Myxophaga: Torridincolidae) and new records from Brazil - Sampaio, Brunno Henrique Lanzellotti; Ferreira-Jr, Nelson (Zootaxa, 2018)
The genus Ytu Reichardt is the most diverse within Torridincolidae, currently with 19 species. Five new species are described herein, four of them from various localities in the southeast of Brazil (type localities in parentheses): Ytu hermes sp. nov. (Brazil, Espírito Santo, Dores do Rio Preto, Pedra Menina, Parque Nacional do Caparaó, Cachoeira Sete Pilões); Ytu hypnos sp. nov. (Brazil, Rio de Janeiro, São Fidelis, Serra Bela Joana); Ytu nyx sp. nov. (Brazil, Espírito Santo, Dores do Rio Preto, Pedra Menina, Parque Nacional do Caparaó, Rio São Domingos, Cachoeira do Aurélio); Ytu thanatos sp. nov. (Brazil, Espírito Santo, Castelo, Parque Estadual do Forno Grande). The other new species, Ytu coeus sp. nov. (Brazil, Espírito Santo, Dores do Rio Preto, Pedra Menina, Parque Nacional do Caparaó, nascente do Rio São Domingos) is described from Brazilian States of Espírito Santo and Ceará, the latter being the first record of this genus in northeastern Brazil. Illustrations of habitus and important diagnostic characters are provided. The new species are compared to other similar species of the genus. New records of some other species of Ytu are presented.